Dosis de fertilización orgánica en la valoración nutricional in vitro EN Moringa oleífera - Romero Alarcón, María Eugenia (2021)
Moringa oleifera has an excellent response in the production of forage to fertilization, with the ability to adapt to territories with hot climates and low rainfall. The importance of using Marango as forage is due to its good nutritional characteristics and its high yield of fresh biomass production. The objective of this work was to evaluate the dose of organic fertilization in the in vitro nutritional assessment of Moringa oleifera. The experimental work was carried out at the “La María” Campus of the Quevedo State Technical University. A complete randomized design (DCA) was used. 16 plots were selected with the following treatments T0= 0 g compost; T1= 770 g compost ha-1 corte-1; T2= 1540 g compost ha-1 corte-1 y T3= 2310 g compost ha-1 corte-1. After 60 days, the forage material of the treatments was collected and 4 repetitions of each plot were collected. The analysis of the bromatological composition of the MS, MO, PC, FDN and FDA was carried out. For digestibility and in vitro degradability, four fistulated bulls were used in the rumen, the protocol recommended by the manufacturer for the DaisyII® incubator was followed, (ANKOM Technology, Fairport, NY-USA A220) (ANKOM, 2004) at a temperature of 39.2 ± 0.5 ºC, using FN ° 57 bags with a pore size of 25 µm and dimensions of 5 x 4 cm made of polyester / polyethylene and 0.30 g of sample of each treatment were deposited and incubated for 6, 12, 24, 48, 72 and 96 h. The degradation of dry matter (DM), organic matter (OM), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were determined by weight difference, and in vitro digestibility was performed at 48 hours incubation. The bromatological composition and in vitro digestibility (p> 0.05) did not show variations in the compost dose. The potential degradation showed differences between treatments (p <0.05), for NDF in T1 (64.15%) and for effective degradation for NDF and ADF in treatments T0 and T1 (46.47 and 38, 70%) respectively. It is concluded that the doses of organic fertilizer (compost) did not influence the bromatological composition, digestibility, the degradation parameters of the nutrients. Keywords: forage, animal nutrition, shrub, compost, kinetics.